Acessibilidade arquitetônica: implicações nos processos de acesso e permanência de estudantes com deficiência na Universidade Federal do Espírito Santo - Francisco, Larissa Littig (2021)
This master's thesis presents some discussions, of the data produced, on this research investigation theme. We set the goal of an analysis of the architectural accessibility of the university considering the implication of guaranteeing access, permanence, and learning process and development of students target audience of Special Education in higher education. We considered the triad “access, permanence and learning and development process” for the constitution of the realization of inclusive education. Our research addressed architectural accessibility, which aims to eliminate physical environmental barriers in homes, buildings, spaces, urban equipment, school, and university spaces; and the attitudinal accessibility, related to all axes of accessibility. The purpose of this research was to problematize the importance of architectural accessibility at the university; and guarantee access, permanence, and the learning and development process of students who are the target audience of Special Education in higher education. Aiming the development of this research, in our methodological path; we opted for a qualitative approach, carrying out a case study at Ufes, with the following instruments: documentary study, observation, photographs, and questionnaires, with open and closed questions, sent by e-mail. Our study is based on Figurational Sociology developed by Elias and other concepts also developed by the author. But for the potential of educational discussions, we dialogue with Freire, who contributes by approaching and discussing the Fundamental Knowledge for Progressive Educational Practice. The investigation results show that Ufes, as part of the social process, consisting of the entire university community (students, professors, and staff), has been moving towards qualifying and guaranteeing the accessibility of students, the target audience of Special Education. Students' narratives show many barriers in the architectural accessibility of university spaces, on the four campuses that make up Ufes. They also considered accessibility promoted the autonomy and acceptance of them in higher education, therefore enhancing the inclusion of Everyone! In our final considerations we argue that accessible and welcoming spaces enhance the learning and development process of students with or without disabilities in higher education.